2019
DOI: 10.5897/jene2018.0735
|View full text |Cite
|
Sign up to set email alerts
|

Flora composition, structure and diversity in the Kimbi Fungom National Park, North West Region, Cameroon

Abstract: The Kimbi Fungom National Park is reported to be relatively less diverse compared to other national parks of Cameroon. This might be due to the configuration of the landscape and habitat types. The main objective of this study is to determine the species composition, structure and diversity in the heterogeneous landscape of the Kimbi Fungom National Park defined by different habitat types. The park was divided into 20 blocks and 10 blocks were randomly selected for this flora survey. In each block, a 1 km line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…There were fewer trees which belonged in DBH classes of 60 cm and above. Similar results were recorded by Zeh et al, (2019). This may be attributed to continuous degradation of the forests due to dominance and falling of bigger trees in addition to other factors like decrease in soil nutrients that limited the sustainability of tree species (Saunders et al, 1991).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…There were fewer trees which belonged in DBH classes of 60 cm and above. Similar results were recorded by Zeh et al, (2019). This may be attributed to continuous degradation of the forests due to dominance and falling of bigger trees in addition to other factors like decrease in soil nutrients that limited the sustainability of tree species (Saunders et al, 1991).…”
Section: Discussionsupporting
confidence: 79%
“…This also corroborates with Lebrun (1936) whose study revealed that the vegetation of the Korup forest was dominated by Fabaceae. It was also reported same of Fabaceae being the most dominant plant family in the Kimbi-Fungom National Park, in the North West Region of Cameroon (Zeh et al, 2019). This confirmed the fact that Fabaceae is always amongst the three most dominant families in the world.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation